Sexualities: Past Reflections, Future Directions - Hines, Sally. author. aut Link
XII, 315 p.
Keywords: This collection examines recent theoretical and methodological debates, shifts in law and policy, and social and cultural changes around sexuality. It sets out new ways of conceptualizing and researching sexuality and explores persistently marginalised and re-traditionalised sexual practices, subjectivities and identities.